Directionality of Wingless protein transport influences epidermal patterning in the Drosophila embryo. - Moline, M.M.; Southern, C.; Bejsovec, A. (Development, 1999)
Active endocytotic processes are required for the normal distribution of Wingless (Wg) protein across the epidermal cells of each embryonic segment. To assess the functional consequences of this broad Wg distribution, we have devised a means of perturbing endocytosis in spatially restricted domains within the embryo. We have constructed a transgene expressing a dominant negative form of shibire (shi), the fly dynamin homologue. When this transgene is expressed using the GAL4-UAS system, we find that Wg protein distribution within the domain of transgene expression is limited and that Wg-dependent epidermal patterning events surrounding the domain of expression are disrupted in a directional fashion. Our results indicate that Wg transport in an anterior direction generates the normal expanse of naked cuticle within the segment and that movement of Wg in a posterior direction specifies diverse denticle cell fates in the anterior portion of the adjacent segment. Furthermore, we have discovered that interfering with posterior movement of Wg rescues the excessive naked cuticle specification observed in naked (nkd) mutant embryos. We propose that the nkd segment polarity phenotype results from unregulated posterior transport of Wg protein and therefore that wild-type Nkd function may contribute to the control of Wg movement within the epidermal cells of the segment.